2015
DOI: 10.1111/asj.12415
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological evaluation of subacute ruminal acidosis (SARA) by continuous ruminal pH monitoring

Abstract: Evaluation of the radio‐transmission pH‐measurement system for monitoring the ruminal pH and subacute ruminal acidosis (SARA) in cattle is described. This is done in order to reveal the possible application of this system for detection and pathophysiological research of SARA by continuous ruminal pH measurement. The possibility of using this system for assessment of the ruminal pH in SARA cattle, and the presence of negative correlation between the ruminal pH and ruminal temperature in heathy and SARA cattle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 51 publications
8
45
0
3
Order By: Relevance
“…Usually, with higher amounts of easily degradable carbohydrates, the ratio of Firmicutes to Bacteroidetes increases, because Firmicutes generally benefit from easily digestible carbohydrates (Kallus and Brandt, 2012), and many gramnegative Bacteroidetes are sensitive to pH (Kampmann et al, 2012). It has also been shown that the relative abundance of Firmicutes in the rumen increased with increasing amounts of concentrate fed (Wetzels et al, 2015;Sato, 2016). In the present study we also found that Firmicutes increased from the baseline to the adaptation, but decreased from the adaptation to the SARA challenge, whereas Bacteroidetes increased from the adaptation to the SARA challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, with higher amounts of easily degradable carbohydrates, the ratio of Firmicutes to Bacteroidetes increases, because Firmicutes generally benefit from easily digestible carbohydrates (Kallus and Brandt, 2012), and many gramnegative Bacteroidetes are sensitive to pH (Kampmann et al, 2012). It has also been shown that the relative abundance of Firmicutes in the rumen increased with increasing amounts of concentrate fed (Wetzels et al, 2015;Sato, 2016). In the present study we also found that Firmicutes increased from the baseline to the adaptation, but decreased from the adaptation to the SARA challenge, whereas Bacteroidetes increased from the adaptation to the SARA challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes, the second most dominant phyla in calves' rumen, may stimulate the development of the digestive tract [109]. In adult cows fed concentrate feed, the relative abundance of Bacteroidetes dropped and cows were more susceptible to SARA [110]. The lower level of Bacteroidetes in calves fed only concentrate could be partly explained by greater feed intakes resulting in low rumen pH.…”
Section: Rumen Microbesmentioning
confidence: 99%
“…However, its overproduction is one of the mechanisms of subacute ruminal acidosis (SARA) creation, which may contribute to damage of the digestive tract and disruption of the optimal ruminal ecosystem, impair nutrients utilization, etc. (Martin et al 2006;Lettat et al 2010;Kim et al 2016;Sato 2016). Calculation of the acetate:propionate ratio is also used when evaluating rumen fermentation (Mirzaei et al 2016;Kim et al 2016).…”
Section: Discussionmentioning
confidence: 99%